FEATURES OF KARAKALPAK MELON VARIETIES WHICH ARE RECOMMENDED FOR DRYING - Abdieva G.M; Karimullaeva M.U (International Engineering Journal For Research & Development, 2020)
Melon-growing in Central Asia is one of the oldest branches of agriculture. The Republic of Karakalpakstan is one of the regions of origin of the most valuable high-sugar varieties of melons. In the ancient oases of Khorezm, Khiva, Nukus, Khojeyli, Kungrad, located in the floodplain of the Amu-Darya river, almost all the existing cultural varieties of melons were created and formed (more than 160) [1].